Mobiluncus species--kultivace, identifikace, vztah k bakteriální vaginóze - Wolfová, J (Ceskoslovenska epidemiologie, mikrobiologie, imunologie, 1991)
The authors present a brief account of the history of the genesis of a new genus of bacteria Mobiluncus. They describe their own experience with the cultivation and identification of this microorganism. From 300 specimens of vaginal smears it proved possible to cultivate Mobiluncus sp. in 15 instances whereby all positive cultivations correlated with the microscopic vaginal picture IIb. The majority of patients where Mobiluncus was proved by cultivation had clinical symptoms of the syndrome of bacterial vaginosis which suggests the participation of this organism in the aetiology of the disease.
Keywords: Vagina; vagina; ženské pohlaví; anaerobní bakterie; Humans; Bacteria, Anaerobic; Vaginitis; Female; vaginitida; lidé